Musculoskeletal physiotherapists' use of psychological interventions: a systematic review of therapists' perceptions and practice. Issue 2 (June 2015) - Alexanders, Jenny; Anderson, Anna; Henderson, Sarah
Abstract: Background: Research has demonstrated that incorporating psychological interventions within physiotherapy practice has numerous potential benefits. Despite this physiotherapists have reported feeling inadequately trained to confidently use such interventions in their day-to-day practice. Objective: To systematically review musculoskeletal physiotherapists' perceptions regarding the use of psychological interventions within physiotherapy practice. Data sources: Eligible studies were identified through a rigorous search of AMED, CINAHL, EMBASE, MEDLINE and PsychINFO from January 2002 until August 2013. Study eligibility criteria: Full text qualitative, quantitative and mixed methodology studies published in English language investigating musculoskeletal physiotherapists' perceptions regarding their use of psychological interventions within physiotherapy practice. Study synthesis and appraisal: Included studies were appraised for risk of bias using the Critical Appraisal Skills Programme qualitative checklist. Meta-analysis was not possible due to study heterogeneity. Results: Six studies, all with a low risk of bias, met the inclusion criteria. These studies highlighted that physiotherapists appreciate the importance of using psychological interventions within their practice, but report inadequate understanding and consequent underutilisation of these interventions. Limitations: These results should be noted with some degree of caution due to various limitations associated with the included studies and with this review, including the use of a qualitative appraisal tool for mixed methodology/quantitative studies. Conclusion: These findings suggest that musculoskeletal physiotherapists are aware of the potential benefits of incorporating psychological interventions within their practice but feel insufficiently trained to optimise their use of such interventions; hence highlighting a need for further research in this area and a review of physiotherapist training.